Using datasets from the Internet for hydrological modeling: an example from the Kucuk Menderes Basin, Turkey - Lacroix, M.; Kite, G.W.; Droogers, Peter (International Water Management Institute, 2000)
Public domain datasets are freely available on the Internet are easy to obtain, and often more up-to-date than those from local sources. This simplifies the modeling process and increases the ability to model basins anywhere in the world, from anywhere with Internet access. Although not all types of data are available, and some conversions may be needed, the information provided does allow for quick and easy simulations of basins. The Semi-Distributed Land-Use Runoff Process (SLURP) hydrological model has been designed to take advantage of such data sources. The application described in this report uses public domain data for topography, land use, seasonal variation in leaf area index (for transpiration) and climate data- all without calibration of parameters.